Image processing technology based on computer vision algorithm - Fan, Mengxia; Liu, Yunna (2022 4th International Conference on Artificial Intelligence and Advanced Manufacturing (AIAM), 2022)
Under the background of information age, image processing technology is a commonly used technology in all walks of life. In order to improve the image correction effect, it can be processed based on computer vision algorithm. This paper introduces the image categories and technical characteristics of computer vision algorithm and image processing technology, discusses the image processing technology based on computer vision algorithm, including computer vision display system and image distortion correction two parts, the effect is good, has high application value. In the past, due to the lack of technological development, objects in the traditional two-dimensional environment can only display the side projection, relatively single, in order to adapt to social progress, technology will continue to develop, so three-dimensional three-dimensional picture emerged at the historic moment, a new display technology appeared. In order to obtain the ideal visual effect, technicians need to implement image processing technology on the basis of computer vision algorithm, express the actual coordinates of objects in three-dimensional space with three-dimensional voxels, and correct the distorted image caused by projection. Compared with the traditional BP neural network, the image processing technology based on computer vision algorithm obviously has more advantages and higher accuracy.